Harmonization of higher education for sustainable development: Southern Africa Development Community experiences - Chikuvadze, Pinias; Mugijima, Samuel (Noyam Journals, 2024)
The world-over, higher education remains a key determinant for scientific and technological development. Hence, Southern Africa Development Community (SADC)’s higher education institutions are considered crucial social organizations in spreading knowledge, and innovation for sustainable development. This study called for inclusion of the qualitative content analysis in an attempt to explore higher education collaboration or partnerships within SADC. Using the AJOL, Scopus, DHTE, DOAJ, Web of Science, and Google Scholar, 60 articles were purposively selected for this review. These available literature sources are accessible on issues around higher education harmonization for sustainable development in SADC for scrutiny. From the content analysis, harmonization was conceptualized as the collaboration, integration or partnership within regional higher education institutions. The rationale for these collaborations or partnerships was to enhance adherence to the agreed-upon higher education conditions and instruments. These created the framework of standards, to facilitate credit transfer and evaluation within SADC’s higher education institutions. From this content analysis, it can be concluded that the harmonization of higher education systems for sustainable development is seen as a spontaneous process subtle to various intricacies, as it permits individual institutions to enjoy the fruits of regional integration. It is in this context, that the researchers recommend the enunciation of SADC’s higher education harmonization for sustainable development guiding procedures vis-a-vis internationalisation. Therefore, this discussion adds voice to the existing argument on the need for higher education institutions in SADC member states to move towards an integrated higher education system.
Keywords: Experiences; Harmonization; Higher Education; Southern Africa Development Community; Sustainable Development